Pengaruh Terapi Kompres Dingin Terhadap Nyeri Post Operasi ORIF (Open Reduction Internal Fixation) pada Pasien Fraktur di RSD Dr. H. Koesnadi Bondowoso (The Effect of Cold Compress Therapy toward Post Operative Pain in Patients ORIF Fracture in RSD Dr. H. - Amanda Putri Anugerah; Retno Purwandari; Mulia Hakam (Pustaka Kesehatan, 2017)
Fracture is a break of continuity of bone, usually caused by trauma or physical exertion. Pain is themost common complaint in patients with fracture. One of the interventions that can reduce fracturepain is giving cold compress using a towel put in ice cubes mixed with water and put it on the skinthat do for 10 minutes. The purpose of this research was to analyze the effect of cold compresstherapy against post operative pain in patients ORIF fracture. This research method was preexperimental with one group pretest-posttest design. The sampling technique was quota samplinginvolving 10 respondents. The independent variable was cold compress therapy and dependentvariable was post operative pain. The data were analyzed using wilcoxon test with significant levelof α = 0,05. Mean of respondent pain score before intervention was 3,7 and score after interventionwas 2,9. The result showed a significant difference between pretest and posttest (p = 0,005). Thisresult indicates that there is significant effect of cold compress therapy on post operative pain inpatients ORIF fracture. Nurse was suggested to apply cold compress therapy as one ofinterventions to decrease post operative pain in patients ORIF fracture.Keywords: ORIF, cold compress, post operative pain